Computational and experimental evaluation of Pisolithus arhizus metabolites targeting major efflux pumps of mastitis-associated Staphylococcus aureus - Hansa Gul; Iram Zahra; Zahida Nasreen; Haris Ahmed Khan; Muhammad Naeem-ul-Hassan; Nouman Ahmad; Nasir Assad; Dawit Kifle; Lennin Garrido-Palazuelos (PLoS ONE, 2026)
Antimicrobial resistance (AMR) in pathogenic bacteria, particularly Staphylococcus aureus , is an increasing global concern in veterinary medicine. The present study evaluated bioactive metabolites from P. arhizus as potential inhibitors of major S. aureus efflux pumps. The methanolic extracts of P. arhizus were profiled using GC–MS to identify the main constituents, and their antibacterial activity against S. aureus was evaluated using a well diffusion assay. The experimental results showed that the crude methanolic extract exhibited a 20 mm zone of inhibition with a MIC of 30 µg/mL. Furthermore, isolated metabolites, octadecanoic acid and compound tentatively identified by GC-MS as 3-(6-methyl-3-pyridyl)-1,5-diphenyl-2-pyrazoline (a pyrazoline derivative), (tentatively identified) demonstrated zones of inhibition of 19 mm each, with MIC values of 30 µg/mL and 40 µg/mL, respectively . In silico analyses, including molecular docking and molecular dynamics (MD) simulations, were performed to examine the binding and stability of 12 fungal metabolites with the major S. aureus efflux pumps NorA, NorB, NorC, and MepA. Binding-free energy estimation by MM-GBSA supported favorable interactions for selected compounds, with pyrazoline and octadecanoic acid showing the most promising profiles. Principal component analysis (PCA), dynamic cross-correlation matrix (DCCM) analysis, and ADMET predictions further suggested stable complex behavior and acceptable drug-likeness features. In general, these results indicate that the P. arhizus metabolites demonstrated antibacterial activity and showed a high binding affinity to efflux pumps in silico , suggesting that they merit further investigation as potential antibacterial agents with predicted interactions toward efflux pump proteins.